Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.

Carbohydrate-based approach for the total synthesis of strictifolione - Ramana, C. V.; Raghupathi, N.; Gurjar, M. K.; Chorghade, Mukund S. (Tetrahedron Letters, 2005)
A chiral pool approach starting with D-glucose, using the Yamaguchi protocol and a Z-selective HWE reaction followed by lactonization, has been applied to execute the total synthesis of strictifolione. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: D-Glucose; double elimination; Horner-Wadsworth-Emmons reaction; lactonization; strictifolione; Yamaguchi protocol

Convenient synthesis of the enantiomerically pure beta-blocker (S)-betaxolol using hydrolytic kinetic resolution - Joshi, Ramesh A.; Garud, Dinesh R.; Muthukrishnan, Murugan; Joshi, Rohini R.; Gurjar, M. K. (Tetrahedron-Asymmetry, 2005)
Enantiopure (S)-betaxolol was prepared in an extremely simple and practical way using hydrolytic kinetic resolution of a terminal epoxide by Jacobsen's catalyst. High enantiomeric purity (99% ee) has been achieved and the method is amenable to industrial scale-up. (c) 2005 Elsevier Ltd. All rights reserved.

Convenient chemoenzymatic synthesis of (1S,7aS)-1-hydroxy-5-oxo-4-(2 `-carboxyethyl)-7a-methyltetrahydro-indane - a key intermediate of steroids - Kalkote, Uttam R.; Purude, A. N.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Molecular Catalysis B-Enzymatic, 2006)
A porcine pancreatic lipase mediated enzymatic hydrolysis of (+/-)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydroindane (5b) furnished (1S,7aS)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (9) and (1R,7aR)-1-hydroxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (8) with > 99% e.e. which on further chemical hydrolysis gave 1 and ent-1, key intermediates of steroids. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemoenzymatic method; Enzymatic hydrolysis; steroids; terpenoids